Digital saint. (New Humanist)
The article reports that Italian computer programmer, Carlo Acutis may become the first saint of his generation, after being beatified by Pope Francis. It mentions that the call for beatification gained momentum soon after his death, as he recorded purported miracles online and helped run websites for Catholic organisations.